Electroacupuncture activated local sympathetic noradrenergic signaling to relieve synovitis and referred pain behaviors in knee osteoarthritis rats - Chen, Wei; Zhang, Xiao-Ning; Su, Yang-Shuai; Wang, Xiao-Yu; Li, Heng-Cong; Liu, Yi-Han; Wan, Hong-Ye; Qu, Zheng-Yang; Jing, Xiang-Hong; He, Wei (Frontiers in Molecular Neuroscience, 2023)
Introduction Recent research has focused on the local control of articular inflammation through neuronal stimulation to avoid the systemic side effects of conventional pharmacological therapies. Electroacupuncture (EA) has been proven to be useful for inflammation suppressing and pain reduction in knee osteoarthritis (KOA) patients, yet its mechanism remains unclear. Methods In the present study, the KOA model was established using the intra-articular injection of sodium monoiodoacetate (MIA) (1 mg/50 μL) into the knee cavity. EA was delivered at the ipsilateral ST36-GB34 acupoints. Hind paw weight-bearing and withdrawl thresholds were measured. On day 9, the histology, dep enrichment proteins, cytokines contents, immune cell population of the synovial membrane of the affected limbs were measured using HE staining, Masson staining, DIA quantitative proteomic analysis, flow cytometry, immunofluorescence staining, ELISA, and Western Blot. The ultrastructure of the saphenous nerve of the affected limb was observed using transmission electron microscopy on the 14th day after modeling. Results The result demonstrated that EA intervention during the midterm phase of the articular inflammation alleviated inflammatory pain behaviors and cartilage damage, but not during the early phase. Mid-term EA suppressed the levels of proinflammatory cytokines TNF-α, IL-1β, and IL-6 in the synovium on day 9 after MIA by elevating the level of sympathetic neurotransmitters Norepinephrine (NE) in the synovium but not systemic NE or systemic adrenaline. Selective blocking of the sympathetic function (6-OHDA) and β2-adrenergic receptor (ICI 118,551) prevented the anti-inflammatory effects of EA. EA-induced increment of the NE in the synovium inhibited the CXCL1-CXCR2 dependent overexpression of IL-6 in the synovial macrophages in a β2-adrenergic receptor (AR)-mediated manner. Discussion These results revealed that EA activated sympathetic noradrenergic signaling to control local inflammation in KOA rats and contributed to the development of novel therapeutic neurostimulation strategies for inflammatory diseases.